1998
DOI: 10.1029/98jd01169
|View full text |Cite
|
Sign up to set email alerts
|

Reducing uncertainties in δ13C analysis of tree rings: Pooling, milling, and cellulose extraction

Abstract: Abstract. Recent developments of on-line methods have provided another boost to the determination of stable isotope ratios in organic material. Along with a significant increase in sample throughput, the sample sizes decrease, both of which are necessary conditions to acquire long time series from limited wood amounts. In view of this new technique we reconsidered the most important factors influencing the measured isotopic signature which are (1) pooling, (2) homogeneity, and (3) cellulose extraction. In most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
150
3
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(174 citation statements)
references
References 18 publications
(9 reference statements)
20
150
3
1
Order By: Relevance
“…This has been reported for stable carbon isotope ratios analysed with annual resolution (Livingston & Spittlehouse 1996;Borella et al 1998;MacFarlane et al 1999) and with ultra-high resolution (Helle & Schleser 2004a). In addition, Loader, Robertson & McCarroll (2003) found that bulk wood is a better climate proxy than a-cellulose.…”
Section: Sampling and Sample Preparationmentioning
confidence: 99%
“…This has been reported for stable carbon isotope ratios analysed with annual resolution (Livingston & Spittlehouse 1996;Borella et al 1998;MacFarlane et al 1999) and with ultra-high resolution (Helle & Schleser 2004a). In addition, Loader, Robertson & McCarroll (2003) found that bulk wood is a better climate proxy than a-cellulose.…”
Section: Sampling and Sample Preparationmentioning
confidence: 99%
“…Therefore, to ensure the annual resolution of the environmental record, only latewood was analysed in this study. The measurements were carried out on wood since 13 C/ 12 C ratios determined in bulk wood showed the same relative variations as in isolated cellulose (Leavitt and Long, 1982;Borella et al, 1998;Loader et al, 2003) and moreover stronger climate response was found for bulk wood compared to cellulose, especially for pedunculate oak, without any temporal offset in the climate response (Loader et al, 2003). Wood slivers (~1-5 mg) were combusted in a Pyrex tube with CuO (Boutton et al, 1983).…”
Section: Stable Carbon Isotope Measurements and Subsequent Correctionsmentioning
confidence: 99%
“…However, strong correlations between D of whole tissue and cellulose have led others to conclude that whole wood provides a good 'climate proxy' (e.g. Borella et al 1998) and whole wood and leaf tissue were used for subsequent analyses in this study. The 13 C/ 12 C ratio (d 13 C) of a 2-mg subsample of whole wood, whole leaf or leaf holocellulose material was determined as described in Macfarlane & Adams (1998).…”
Section: Carbon Isotope Analysesmentioning
confidence: 99%